2017
DOI: 10.1111/pai.12732
|View full text |Cite
|
Sign up to set email alerts
|

Food allergy and attitudes to close interpersonal relationships: An exploratory study on attachment

Abstract: Clinicians should be aware of implications of insecure attachment for health and illness. They should support patients in limiting social impairment finding a balance between safety and psychologic well-being.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“…The usefulness of individual school healthcare plan in allergic children has been stressed earlier in this Journal, 14 and it has also been shown that a precise diagnosis allowing appropriate management in the community has a major effect on the child and its family. [15][16][17][18] Also, a thorough diagnosis should be pursued: Food challenges are most contributable to the diagnosis and should not be delayed. 19 Johannes Savolainen…”
Section: Danielle Cliffordmentioning
confidence: 99%
See 1 more Smart Citation
“…The usefulness of individual school healthcare plan in allergic children has been stressed earlier in this Journal, 14 and it has also been shown that a precise diagnosis allowing appropriate management in the community has a major effect on the child and its family. [15][16][17][18] Also, a thorough diagnosis should be pursued: Food challenges are most contributable to the diagnosis and should not be delayed. 19 Johannes Savolainen…”
Section: Danielle Cliffordmentioning
confidence: 99%
“…After the diagnostic procedure and a 2‐year follow‐up, more than 65% of the study subjects could suspend their avoidance diet, resulting in a significant reduction of costs. The usefulness of individual school healthcare plan in allergic children has been stressed earlier in this Journal, and it has also been shown that a precise diagnosis allowing appropriate management in the community has a major effect on the child and its family . Also, a thorough diagnosis should be pursued: Food challenges are most contributable to the diagnosis and should not be delayed …”
mentioning
confidence: 99%
“…They should support patients in limiting social impairment finding a balance between safety and psychologic well-being. 41 Changes in patient quality of life during oral immunotherapy for food allergy have been studied. 42 The…”
Section: Pre Venti On and Control Of Food Allergymentioning
confidence: 99%
“…Clinicians should be aware of the implications of insecure attachment for health and illness. They should support patients in limiting social impairment finding a balance between safety and psychologic well‐being . Changes in patient quality of life during oral immunotherapy for food allergy have been studied .…”
Section: Prevention and Control Of Food Allergymentioning
confidence: 99%
“…99 Patients with food allergy were more likely to exhibit attachment avoidance and discomfort, with close relationships in a cross-sectional European study, highlighting the need to carefully balance safety and psychological well-being. 100 The effect of OIT on QoL was examined, and investigators observed that patients with impaired QoL at baseline improved significantly despite the burdensome demands of therapy, whereas some patients with acceptable QoL at baseline had deterioration because of the demands associated with OIT. 101…”
Section: Effects Of Food Allergymentioning
confidence: 99%